The Effect Of Service Quality, Trust And Customer Retention On Customer Loyalty At Pt Relasi Laksana Wisata - Sofia Alifah (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The Umrah and Hajj travel business in Jember is growing rapidly with intense competition, so PT Relasi Laksana Wisata must improve its service, trust, and customer retention to maintain loyalty. This study aims to analyze the influence of service quality, customer trust, and customer retention on customer loyalty at PT Relasi Laksana Wisata, an Umrah and Hajj travel agency in Jember Regency. The research method uses a quantitative approach with data collection through questionnaires to 130 pilgrims who became the research sample. Data analysis was performed with multiple linear regression using SPSS. The results show that service quality, customer trust, and customer retention have a positive and significant effect on customer loyalty. In addition, customer satisfaction acts as an intervening variable that strengthens the relationship between these three variables and customer loyalty. These findings indicate that improving service quality, building trust, and maintaining customer retention are key strategies for PT Relasi Laksana Wisata in maintaining and increasing pilgrim loyalty amidst increasingly fierce competition in the pilgrimage travel service business. Practical implications and suggestions are also provided for service development and strengthening customer loyalty.